Developing Thai Reading and Writing Skills through Thai Language Conservation Camp Activities for Students in Lower Secondary Schools, Satuek School in Buri Ram Province, and Nadee Witthaya School in Surin Province - Sarasup, Wipawan; Boongthong, Siriluck; Pagdee, Supachai; Siangchin, Janjira; Prathuangset, Athiporn; Rueangsuwan, Nittaya; Santawong, Siraprapa (Journal of Human and Society, Sisaket Rajabhat University, 2024)
This research article presents the development of Thai reading and writing skills through Thai language conservation camp activities for students in lower secondary school, Satuek School in Buri Ram Province, and Nadee Witthaya School in Surin Province The objective is to compare Thai reading and writing skill achievement before the utilization of Thai conservation camp activities, and to assess satisfaction with these activities. The target group comprises 169 lower secondary school students form Satuek School, Buri Ram Province, and 275 students from Nadee Wittaya School, Surin Province. This sample is selected through purposive sampling. The tools used were included a test to measure Thai reading and writing skills, as well as a satisfaction assessment form. The statistics utilized in the research encompass the comparison of achievement in Thai reading and writing skills before and after studying, employing statistical methods such as the t-test (Dependent), and assessing satisfaction in organizing Thai conservation camp activities. The data were analyzed using mean ( ) and standard deviation (S.D.). The research results found that 1. Satuek School Buri Ram Province, students demonstrated higher achievement in Thai reading and writing skills after participating in Thai conservation camp activities compared to their performance before studying, with statistical significance at the .05 level. Additionally, students expressed the highest level of satisfaction with the Thai conservation camp ( = 4.72). 2. Nadee Wittaya School in Surin Province, students demonstrated higher achievement in Thai reading and writing skills after participating in the activities of the Thai conservation camp compared to their performance before studying, with statistical significance at the 0.05 level. Additionally, the students expressed the highest level of satisfaction with the Thai language conservation camp ( = 4.51).